SUSTAINABLE DEVELOPMENT BASED TOURISM DEVELOPMENT IN WONOLOPO, SEMARANG - Falih Suaedi; Jusuf Irianto; Eko Supeno; Bintoro Wardiyanto; Sunaryo Haryono; Antun Mardiyanta; Gitadi Tegas Supramudyo; Rochyati Wahyuni Triana; Erna Setijaningrum; Sulikah Asmorowati; Nanang Haryono; Philipus Keban; Putu Aditya Ferdian Ariawantara; Agie Nugroho Soegiono (Universitas Airlangga, 2023)
The progress of tourism is heavily influenced by the professionalism and existence of its institutions (tourism institutions). In this community service, the Airlangga University Public Administration team partnered with the Diponegoro University Public Administration team to assist MSME partners in Wonolopo Semarang. The problem with partners is the need to strengthen tourism institutions and expand the marketing of MSME products including herbal medicine villages, flora villages selling ornamental plants, and so on. Wonolopo has 10 tourism awareness groups from 8 thematic villages. The solution to the partner problem is the transfer of knowledge of tourism institutional development. There are three choices of institutional forms, namely tourism awareness groups, cooperatives and BUMDesa. The solution to the second problem is information and communication technology-based marketing with Linktree which is shared on social media and using digital marketing platforms. The results achieved after the community service was carried out were that 98.3% of MSME actors and tourism managers in Wonolopo Semarang had increased their abilities in developing tourism institutions and digital marketing innovation, as much as 1.6% needed to be improved. For this reason, more intensive assistance is needed for partners in Wonolopo, Semarang.